The Effect of Artificial Saliva on The Surface Roughness of Different Esthetic Archwires (An in Vitro Study) - Muayad, Noor S; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2017)
Background:The demand for esthetic orthodontic appliances is increasing so that the esthetic orthodontic archwires were introduced. This in vitro study was designed to evaluate the surface roughness offiber-reinforced polymer composite (FRPC) archwires compared to coated nickel-titanium (NiTi) archwires immersed in artificial saliva.Materials and Methods:Three types of esthetic orthodontic archwires were used: FRPC (Dentaurum), Teflon coated NiTi (Dentaurum) and epoxy coated NiTi (Orthotechnology). They were round (0.018 inch) in cross section and cut into pieces of 15 mm in length.Forty pieces from each type were divided into four groups; one group was left at a dry condition and the other three groups were immersed in artificial saliva (pH=6.75 Â± 0.015) at 37ÂºC for 1, 14 and 28 days intervals. The AFM was used to evaluatesurface analysis of all samples.ANOVA, Kruskal-Wallis, LSD and Mann-Whitney U tests were used to identify and localize the source of differences among the groups. Results:At each immersion period, FRPC wires exhibited the highest Ra among the study groups, except at 28 days immersion period where the Teflon coatings were the roughest. On the other hand, the least rough surfaces were the epoxy coatings when compared to analogous esthetic archwires, except at 1 day immersion period where the Teflon coatings had the least roughness. However, statistically non-significant differences were found between Teflon and epoxy at the dry condition and the 1 day immersion.Conclusions:The epoxy coated archwires are the best and the most appropriate esthetic orthodontic alignment archwires in term of the least surface roughness initially and over the course of study period.